Thésée. Tragédie - Quinault, Philippe 1635-1688 (Paris Ballard, 1754)
This is the libretto for the production that featured the Slodtz' brothers "Temple de Minerve" stage set currently preserved at the Petit Théâtre de la Reine in Versailles. See Dominique Lauvernier, ‘Le Temple de Minerve : un décor de scène du fonds des Menus Plaisirs datant de 1754’, Bulletin de la Société de l'Histoire de l’Art Français Année 1993 (1994), 127-148.
Some text fragments are pasted over with blank papers, and pages 41-42 are missing, all indicating cuts
Premiered in 1675 with music by Jean-Baptiste Lully
Purchased by Ton Koopman from Wurlitzer, New York
Covered with gold paper indicating "1754" and "Quinault"
Représentée devant le Roi à Fontainebleau le ? octobre 1754
Keywords: Lully, Jean-Baptiste -- 1632-1687; Château de Fontainebleau (France); 17th Century (1601-1700); 18th Century (1701-1800); Opera; Libretto; Mythology; Fontainebleau (France)